Augustine's confessions conversion and consciousness - Craig, Robert H. (Lexington Books, 2020)
"Robert Craig analyzes the Confessions as an allegory showing Augustine's state of mind or disposition through space/time. His use of different personas, schools of thought, and metaphysical constructs shows the inadequacy of Plato's consciousness model of the cave to truly describe human ratiocination within consciousness in its totality."
Keywords: Augustinus, Aurelius -- Heiliger -- 354-430 -- Confessiones; Kommentar; Augustine / of Hippo, Saint / 354-430 / Confessiones; Confessiones (Augustine, of Hippo, Saint)